Cytotaxonomic diagnosis of Trichomycterus diabolus (Teleostei: Trichomycteridae) with comments about its evolutionary relationships with co-generic species - Torres, Rodrigo A.; Oliveira, Claudio [UNESP]; Foresti, Fausto [UNESP] (Sociedade Brasileira de Ictiologia, 2004)
São descritos o cariótipo e a localização das regiões organizadoras de nucléolo (Ag-NOR) de uma amostra de Trichomycterus diabolus, coletada no córrego Hortelã (Botucatu, São Paulo, Brasil). A espécie apresentou 2n=56 cromossomos (42 metacêntricos, 12 submetacêntricos e 2 subtelocêntricos) e as regiões organizadoras de nucléolo localizadas próximas ao centrômero, no braço longo do maior par metacêntrico. A ocorrência de 2n=56 cromossomos em Trichomycterus diabolus é uma característica interessante, uma vez que, até o momento, todas as espécies cis-Andinas cariotipadas apresentaram 2n=54 cromossomos, enquanto que quase todas as espécies trans-Andinas apresentaram números diplóides diferentes. É discutida a possível origem desta inesperada estrutura cariotípica.

The karyotype and the Ag-NOR location of a sample of Trichomycterus diabolus collected in the córrego Hortelã (Botucatu, São Paulo, Brazil) are described. The species exhibited 2n=56 chromosomes (42 metacentrics, 12 submetacentrics and 2 subtelocentrics) and the nucleolus organizing region located near to the centromere on the long arm of the largest metacentric pair. The presence of 2n=56 chromosomes in T. diabolus is an interesting characteristic since until now all cis-Andean species karyotyped presented 2n=54 chromosomes while almost all trans-Andean species presented different diploid numbers. The possible origin of this unexpected karyotypic form is discussed.
Keywords: Trichomycterinae; karyotype; chromosome evolution; fish cytogenetic